NEIGHBOURHOOD ON THE SPECIALIZATION DIVERSITY OF SIX MAJOR BRAN AND DAMPNESS CHANGE IN NEPAL - Kanawha K. Chaugai (International Scientific and Current Research Conferences, 2022)
Resource Nepalese farmers spread across different agro-natural zones keep up enormous species and varietal assortment of different harvests in their property. Anyway, no assessments have been embraced now to assess why farmers proportion and keep up colossal agro-biodiversity, the level of agro-ecological abundance, species luxury, surveyed loss of standard arrangements and threats to the lack of on-farm agro-biodiversity. Information on the amount of collections created by the farmers for six critical staple harvests were accumulated from nine district and twenty sub-locales spread across six particular agro-regular zones of the country to grasp farmers clarifications behind keeping up on-farm crop assortment, measure agro-ecological abundance, species excess and the overall loss of standard arrangements, to understand the famers' level of care on natural change and the different threats to manage assortment. The results from this assessment exhibited that an amazing 93% of the respondents manage and involve agro-bio enhancement for family food security and occupation.